PERAN KELUARGA DALAM MENDAMPINGI ANAK BELAJAR DI RUMAH PADA SISWA KELAS I DI RT 05 DUKUH KUPANG GANG XV SURABAYA - Ade Windari; Dian Kusmaharti; Cholifah Tur Rosidah (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
This research is motivated by the role of the family in accompanying children to learn by paying attention to aspects of learning behavior, namely psychomotor, affective, cognitive students. During the Covid-19 pandemic, the role of families, especially parents, is to accompany children to learn when learning is done online. With the research title, the role of the family in accompanying children to study in grade 1 students at RT 05 Dukuh Kupang Gang XV Surabaya. Based on the results of the validity of observation data, interviews and questionnaires/questionnaires on the role of the family in accompanying children to study at RT 05 Dukuh Kupang Gang XV Surabaya with "very good" psychomotor, affective and cognitive learning behavior. From a comparison of the three data collection techniques, namely the results of unstructured observations, the researcher saw firsthand the activities of the family's role when accompanying children was very good, the researcher continued with an unstructured interview by asking several questions, the results of the interview were very good, the informant was very honest and open to researchers, followed by filling out a questionnaire / questionnaire that researchers have presented with excellent results.Keywords: Role of Family, aspects of learning behavior.